Evaluation of MicroRNA-451a Expression in Lupus Nephritis - Laura Christiani; Dominica Pita Sari; Hani Susianti; Umi Kalsum; Kusworini Handono; Emanuel Hananto (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
The pathogenesis of Lupus Nephritis (LN) is still unclear, causing difficulties in diagnosis and therapeutic management. Recent studies have suggested that microRNAs (miRNAs) may play an important role in the pathogenesis of LN. However, the role of miRNA-451a in LN has not been widely studied and known, and there is controversy in the results of studies that have been done. This study aimed to analyze the expression of miRNA-451a in LN and lupus without nephritis and to evaluate its correlation with hemoglobin levels, leukocyte count, leukocyturia, and erythrocyturia. Samples from 45 lupus participants were collected, consisting of 22 with LN and 23 without nephritis. The expression of microRNA 451a was determined by reverse transcriptase real-time PCR. Renal disorder criteria based on ACR criteria. Statistical analysis using Mann-Whitney, Spearman correlation, ROC curve, and table 2X2. MiRNA-451a expression in LN (median 0.31; range 0.06-7.21) was lower than in lupus without nephritis (median 1.31; range 0.07-13.26) with a significant difference (p=0.041). The cut-off value for comparing the two groups was 0.7531 with an accuracy of 75%. The correlation between miRNA 451a expression and hemoglobin levels, blood leukocyte count, erythrocyturia, and leukocyturia showed no significant correlation (p > 0.05). MicroRNA-451a expression in lupus nephritis was lower than in lupus without nephritis.